The profane sphere of All Saints’ Day and the social aspects of cemeteries - Tanaś, Sławoj (Turyzm/Tourism, 2020)
The modern pop-culturization of All Saints’ Day has encouraged the author to explore the profane sphere of this festival, using selected examples from Łódź cemeteries, as well as to write a short comparative description of a Latin American festival honouring the dead celebrated in early November. In the 20th century, visiting cemeteries in Poland on 1st November acquired some attributes of recreation and cultural tourism, visible in the atmosphere of a country fair and the ludic character of the cemetery surroundings, as well as the visitors’ commemorative, contemplative and cognitive motivations. Due to cultural changes, All Saints’ Day is increasingly perceived as a tourist event or even a cultural tourism product. The article presents a comparative description of the All Saints’ Day celebrations in Poland and the Day of the Dead in Latin America, and an analysis of visitors at selected Łódź cemeteries along with a description of the cemetery surroundings on 1st November 2019. The author has used unpublished research results from 2004, as well as discussing the secular and recreational aspects of All Saints’ Day.